Índices de calidad de habitat y macroinvertebrados en siete Cuencas del Parque Nacional Yanachaga Chemillén y su Zona de Amortiguamiento:: conservación y manejo del bosque ribereño en el Perú - Trama, Florencia Andrea (2020)
We present the characterization of the aquatic environment, riparian ecosystem and macroinvertebrate communities in 7 basins of the west slope of the Yanachaga Chemillén National Park (PNYCh). The CERA protocol, including the Andean Biotic Index (ABI), the Fluvial Habitat Index (IHF), the Andean Creek Index (Qbr-And) were estimated and the combination of these 3 indexes allowed to calculate the Ecological Status Index of Andean Rivers (ECOSTRIAND) at each sampling point. Additionally the FBI and BMWP-Col indexes were calculated. Sampling was carried out in the 7 basins, between 1800 and 2500 meters of altitude, including the upper basins inside the PNYCh, in the middle and lower basins, both in the buffer zone of the park. We found 179 taxa, 66 families and 14 orders in all basins evaluated. Within the PNYCh, the values of IHF and Qbr-And were optimal, but to go down basins, the indexes generally were decreasing in quality. The IBA was very good in all basins and all sampling points. However, when the 3 indexes were combining, the ECOSTRIAND index decreased, changed from very good to good and regular in some basins. The final results show that the ecological status index decreased as it moves away from PNYCh, this is associated with a greater riparian forests disturbance. Finally, we discussed the legal protection of this type of forest in several countries of America and specifically in Peru.